Factors Affecting the Purchase Decision of Investors in the Residential Property Market in Malaysia - Lip Sean, Saw; Teck Hong, *Tan (Journal of Surveying, Construction and Property, 2014)
The objective of the paper is to determine the key factors that investors consider before making an investment decision to purchase a residential property. In this study, 200 self-administered questionnaires were distributed to respondents who have obtained or transacted more than one (1) residential property for the past three years. Only 105 survey forms were returned and used in generating the analysis. Locational, neighborhood, structural and financial factors were taken into consideration in this survey. The results revealed that locational, financial and structural factors do affect property investors in making their purchases. By understanding the motivation behind purchasing residential properties, investors would be able to gauge the factors that matter most before investing in property.